Sami history of ideas around 1700: Fragments of an Unwritten Study - Rydving, Håkan (Nordlit, 2025)
Most of the earliest sources to Sami thinking are secondary. The information is above all found in reports from court proceedings and in texts by missionaries. Despite the problems related to source criticism, these sources give interesting examples on two levels, both about how different noaiddit, ritual specialists and cultural guides, formulated their ideas about the human being, the world, and the colonial situation, and, from some areas, in addition examples of thinking of other Sami, both men and women. The article gives a short overview of the source material and then takes up two examples, (1) what we can know about Sami thinking about the human being, nature, and the world in the Lule and Ume Sami areas during the 1670s thanks to the texts by one of the few Sami of that time who wrote down Sami ideas about such themes, Ánndarisa Nijlas (Nicolaus Lundius), and (2) the fragments of a ‘Philosophy from Below’ that were collected in Njaarke (Namdalen) in the South Sami area during the 1720s.
Keywords: early Sami ideas about the world and the human being; fragmentary sources; Nicolaus Lundius; Njaarke (Namdalen); ‘philosophy from below’